2004
DOI: 10.1091/mbc.e04-07-0579
|View full text |Cite
|
Sign up to set email alerts
|

Megator, an Essential Coiled-Coil Protein that Localizes to the Putative Spindle Matrix during Mitosis inDrosophila

Abstract: We have used immunocytochemistry and cross-immunoprecipitation analysis to demonstrate that Megator (Bx34 antigen), a Tpr ortholog in Drosophila with an extended coiled-coil domain, colocalizes with the putative spindle matrix proteins Skeletor and Chromator during mitosis. Analysis of P-element mutations in the Megator locus showed that Megator is an essential protein. During interphase Megator is localized to the nuclear rim and occupies the intranuclear space surrounding the chromosomes. However, during mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 32 publications
8
111
0
Order By: Relevance
“…This seems to be an evolutionarily conserved interaction, because small interfering RNA-induced depletion of Tpr (the vertebrate orthologue of yeast Mlp1/2-Drosophila Mtor) in HeLa cells significantly reduces Mad2 labeling at the NE (our unpublished data). Our in vivo study further revealed that in syncytial embryos, a fraction of GFP-Mad2 is found within the spindle area in metaphase and subsequently localizes between the two reforming nuclei during telophase ( Figure 7), localizations similar to that of Mtor (Qi et al, 2004). It is thus conceivable that an interaction between Mad1-Mad2 and Mtor may also occur at this stage of mitosis.…”
Section: Mad1 and Mad2 During Drosophila Mitosissupporting
confidence: 60%
See 3 more Smart Citations
“…This seems to be an evolutionarily conserved interaction, because small interfering RNA-induced depletion of Tpr (the vertebrate orthologue of yeast Mlp1/2-Drosophila Mtor) in HeLa cells significantly reduces Mad2 labeling at the NE (our unpublished data). Our in vivo study further revealed that in syncytial embryos, a fraction of GFP-Mad2 is found within the spindle area in metaphase and subsequently localizes between the two reforming nuclei during telophase ( Figure 7), localizations similar to that of Mtor (Qi et al, 2004). It is thus conceivable that an interaction between Mad1-Mad2 and Mtor may also occur at this stage of mitosis.…”
Section: Mad1 and Mad2 During Drosophila Mitosissupporting
confidence: 60%
“…Drosophila NPC disassembly was completed by metaphase and preceded lamina depolymerization, a property shared by C. elegans embryos (Lee et al, 2000). Compared with Nup107, ketel GFP (which, as discussed above, likely interacts with peripheral FG-Nups), as well as Nup153 and Mtor (the Drosophila orthologue of Tpr; Qi et al, 2004), two asymmetrically localized nuclear basket Figure 8. Association of Mad2 with the NPCs at the end of mitosis is a two-step process.…”
Section: Npc Disassembly and Reassembly In Drosophila Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…5 Additionally, they have retained similar functions to those in other eukarya, by creating heterochromatin free zones around nuclear pores that are evident by electron microscopy in all eukaryotic nuclei, as well as recapitulating interactions with the spindle organizer. 4,38,[79][80][81] Thus, in conjunction with divergent lamin-like proteins, 35,82 and unconventional kinetochores, 83 it seems that the trypanosome nucleus uses unique protein complexes in parallel with conserved core elements such as the spindle microtubules and outer kinetochore components, Ndc80/Nuf2 to facilitate trypanosome biology. 84,85 Did trypanosomes retain an ancient symmetric assembly or reconfigure their molecular biology through the loss of introns and individual gene promoters (Fig.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%